2019
DOI: 10.2298/fil1903655p
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization rule applied on accelerated double step size optimization scheme

Abstract: A hybrid accelerated model with two step length parameters for solving unconstrained optimization problems is presented. Applied hybridization process involves an efficient three term hybrid method. The accelerated double step size model is taken as guiding operator in this hybridization process. Defined method is convergent on the set of uniformly convex functions as well as on the set on strictly convex quadratics. We display a Dolan Moré performance profiles of derived iteration and of some other comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…There are many well-known conjugate gradient methods, such as [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][34][35][36][37][38][39][40][41][42]. In [12], the iterative formula of three-term conjugate gradient method is…”
Section: New Three-term Conjugate Gradient Methods For Smooth Casementioning
confidence: 99%
See 1 more Smart Citation
“…There are many well-known conjugate gradient methods, such as [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][34][35][36][37][38][39][40][41][42]. In [12], the iterative formula of three-term conjugate gradient method is…”
Section: New Three-term Conjugate Gradient Methods For Smooth Casementioning
confidence: 99%
“…For three-term conjugate gradient methods [12][13][14][15][16][17][18][19][20][21][22] and the related methods [23][24][25][26] posse low memory requirement and simple implementation, conjugate gradient methods are often used for solving unconstrained optimization problems. Recently, many researchers have presented kinds of three-term conjugate gradient method for solving the unconstrained optimization problems.Hence, we consider using three-term conjugate gradient method to solve the finite minimax problems.…”
Section: Introductionmentioning
confidence: 99%
“…where T : Ω −→ Ω is a mapping defined on nonempty convex subset Ω of a normed space E, a k and v k are sequences determined by the iteration (16), and {η k } is the sequence of positive numbers in (0, 1). Following that, in [14], the hybridization rule in [17] is applied to the double step length scheme in order to improve the convergence properties of the double step length method in [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the literature reviewed above, it can be concluded that using the hybridization process is an excellent way to improve the convergence properties and numerical experiments of some existing methods. Therefore, motivated by the idea presented by Petrović in [14] and the approximation in (14), this paper aims to develop a hybrid double direction and step length method for solving a system of nonlinear equations via…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation